ITS 2 and RNA secondary structure-based analysis reveals a clear picture on phylogeny of South Indian Salacia spp. (April 2021) - Anaz K, Muhammad; N., Sasidharan; A., Remakanthan; M.V., Dilsha
Graphical abstract: Highlights: Phylogeny of South Indian Salacia deduced by ITS 2 marker. Taxonomic identification problems were existed in this group. And that couldnt be resolved by conventional methods alone. We incorporated molecular tools for correct identification in this group. We could incorporate barcoding, which is recent in identification is included in this paper, as a part of that ITS 2 amplification is done in the genus Salacia with good results. This paper covers primary sequence and secondary structure based analysis of ITS 2 gene, based on which, we could solve the taxonomic identification problems in this group.. Abstract: The genus Salacia (Celastraceae) consists of many important medicinal plants used mainly against type II diabetes. Segregation and delimitation of species is difficult based on morphological features alone. DNA barcoding is the most effective and emerging method of molecular identification. It was reported that ITS2 has better discriminating power in the genus Salacia in comparison to other barcode loci. This paper describe the analysis of sequence and structural information of ITS2 to discriminate the species of Salacia . A total of 8 species of Salacia in South India and the available sequences in NCBI database were taken for the present study. NJ method based phylogenetic trees were constructed using MEGAX with primary sequence as well as using sequence and secondary structural information. Primary structure based phylogeny did not give much information whereas the dendrogram based on sequence and structural information was more informative to decipher the phylogeny of South Asian species of Salacia . The present study revealed some interesting facts regarding the genus. Secondary structure of the ITS2 sequence of S. chinensis reported from Kerala differs consistently from that of S. chinensis reported from other parts of India and of South Asia. Probably the S. chinensis in Kerala, India has diverged a lot from the original S. chinensis . ITS2 sequence of S. reticulata reported from Sri Lanka was identical to S. chinensis reported by other groups from Thailand and Udupi, India. The molecular level identity of ITS2 sequence of S. chinensis with S. reticulata suggest merger of the two species. ITS2 sequence of S. beddomei is only reported from Kerala, India showed it to be identical to S. macrosperma . This observation points to a mistaken identity of S. beddomei which could be elusive from Kerala. Phylogenetic trees constructed based on sequence and structural features of ITS2 suggest that the ancestor species of S. chinensis diversified in two evolutionary lines. One line leads to the present day S. chinensis and the other line further diversified and lead to the rest of the present day Salacia species.